Organizing U.S. foreign aid : confronting the challenges of the twenty-first century - Lancaster, Carol (Brookings Institution Press, 2005)
"Recommends fundamental reorganization of U.S. foreign aid, currently based on outsourcing and management for results, in favor of a more unified approach emphasizing development education, stringent evaluation, and a new approach to contracting"--Provided by publisher
Keywords: Economic assistance, American.; Aide économique américaine.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Economic assistance, American